(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The problem of the research was the lack of interest of the Iraqi commercial banks in the credit inquiry and the study of the credit ability of customers and the collection of information about them, which makes the process of granting credit permeated with many risks, and the soundness of decision-making by the bank management, and it was summarized in a number of questions, the most important of which are: Is there a relationship to the inquiry system Credit and exchange of information about the customer by the bank before granting credit in the efficiency of decisions to grant cash credit? The research also aimed to define the role of banking inquiry and the exchange of credit information in enhancing the efficiency of the credit decision taken by the banking system, in order to ensure the safety of payment and non-defaulting. Of a total of (34) banks listed in the Iraq Stock Exchange, which are (Al-Ahly Bank of Iraq, Middle East, United Investment, Assyria International, Commercial Gulf, Sumer Commercial, Babel), and the use of the statistical program (SPSS V.25) in the analysis of the tool Research (questionnaire) and testing research hypotheses. The research reached a set of results, the most important of which are: the existence of a significant correlation of the variable of the credit inquiry system on the variables of creditworthiness, with its five dimensions, in addition to that the process of credit inquiry, analysis and study of creditworthiness criteria is the most important stage of granting credit, which enables the concerned parties in the bank From making credit decisions based on accuracy and objectivity in dealing with credit information, and then this provides the possibility for banks to make their credit decisions correctly without exposing them to credit risks.